Unkept Promises: On the Implementation of the OECD Anti-Bribery Convention in Korea - Dae Un Hong; Jae Sun Kim (Laws)
While the Organization for Economic Cooperation and Development (OECD)’s Anti-Bribery Convention is often considered a success in the fight against global corruption, ensuring its implementation remains challenging. As evidenced by the sustained decline in Transparency International’s ratings, the Korean government does not actively enforce anti-bribery legislation against companies and individuals engaged in business activities abroad. To support this argument, this article reviews the Korean legal apparatus designed to control foreign bribery and examines why the relevant authorities have insufficiently enforced them. Specifically, this paper discusses the Foreign Bribery Prevention Act, its legislative history, how the Korean legislature has failed to implement the OECD Working Group’s recommendations in a timely manner, and the consequences of this failure. Through a case study, this paper compares the practices of Korean law enforcement authorities with those of their counterparts abroad, particularly in the United States. This paper also illustrates how the traditional leniency of Korean prosecutors and judges toward bribe giving, especially by large conglomerates, has affected the enforcement of the relatively new legal apparatus designed to combat bribery of foreign public officials. Furthermore, a cultural leniency toward bribery, coupled with the Korean government’s unwillingness to raise public awareness of foreign bribery crimes and their punishments, poses a significant challenge to combating foreign bribery.